Factors influencing consumers' purchasing behaviour towards organic rice in Malaysia - Ibitoye, Olusola Olugbenga; Mohd Nawi, Nolila; Man, Norsida; Kamarulzaman, Nitty Hirawaty (IDOSI Publications, 2014)
Although certain insights have been gained from past studies on the factors influencing consumers’ purchasing intention towards organic food, not much effort have been made to understand their purchasing intention towards organic rice. This study aimed to explore the factors influencing consumers’ intentions towards the purchase of organic rice. A structured questionnaire using 5-point Likert scales were administered to 334 randomly selected consumers. Data collected were analysed using descriptive analysis and exploratory factor analysis. The result showed health, food safety and environmental benefits as the most important factor influencing consumer’s preferences towards organic rice followed by the other three factors namely organizational interventions, market and packaging. This finding would help stakeholders in the organic rice industry to understand the underlying pattern of consumer behavioural intention and decision towards purchasing organic rice in Malaysia.